Design of a pre-stretched tension Hopkinson bar device: Configuration, tail corrections, and numerical validation. (November 2016) - Haugou, G.; Leconte, N.; Morvan, H.
Highlights: The proposed configuration ensures no overlapping of the elastic waves. A typical tail of pre-stretched bars is identified. Such a tail affects the material law characterization based on the elastic waves. Two analytical methods are proposed and validated to correct the tail. A numerical model enables the experiments to be predicted with or without the tail. Abstract: The use of Hopkinson bar device is suitable for the characterization of high ductility metallic alloys up to fracture at moderate strain rates. Since a fairly long duration time is required, the pre-stretched technique has been chosen. However, elastic wave overlapping at strain gauges is common for such apparatus. A configuration of the apparatus to ensure that no superposition of the elastic wave system develops along the incident bar is thus proposed so as to fulfil standard data analysis requirements, i.e., without any assumptions. However, a drawback of the proposed device is that the pre-loading conditions generate a tail propagating along the incident bar. Although tails also exist in Kolsky bars, the tail identified here in pre-stretched bars is far longer and it significantly affects the strain versus time evaluation, and therefore the material laws based on elastic wave measurements. Both analytical corrections and technological solutions are proposed to cancel the tail. The analytical corrections consist of either rebuilding the reflected pulse based on strain continuity or in subtracting the tail from the raw reflected signal. The experiments have enabled a numerical model to be correlated by modelling the tail, which follows a second order polynomial evolution. By suppressing the tail from the finite element model, an ideal configuration is recovered. The ideal FE configuration finally allows the proposed analytical corrections to be validated and the proposed technological solution to be evaluated.